FAKTOR YANG MEMPENGARUHI KUNJUNGAN MASA NIFAS DI BPM YUNI WATI.KOTA PEKANBARU - Lisviarose; Komaria Susanti; Nafila Darhesta (Universitas Pahlawan Tuanku Tambusai, 2022)
ABSTRACT The postpartum period is a vulnerable period for mothers, about 60% of maternal deaths in Indonesia occur after childbirth and almost 50% of deaths during the puerperium occur in the first 24 hours after delivery, including complications during the puerperium. Problems during the puerperium will have an impact on the welfare of the baby born, because the baby will not get maximum care from his mother. The purpose of this study was to determine the factors that influence postpartum visits at the independent practice midwife